Factors Correlated to Job Stress among ICU Nurses in Surabaya Indonesia - Yulis Setiya Dewi; Rachmat Hargono; Ainur Rusdi (Jurnal Ners, 2019)
Introduction: Job stress is a major barrier to the attainment of safety, health, andwellness among nurses. Understanding factors job stress among nurses is veryimportant to provide alternatives solution to ease the stress in the future. However,there are limited studies with respect to factors related to stress in Intensive CareUnit (ICU) nurses particularly in Indonesian context. This study aimed to identifyfactors correlated to job stress among ICU nurse in three public hospitals.Methods: A correlational study was carried on ICU nurses who hands-on ICUnursing care. Data were collected using questionnaires. Descriptive statistic andSpearman correlation were used to analyze the correlation between perceived jobburden, working condition, quality of nursing work life, perceived organizationalsupport, and stress among ICU nurses.Results: A total of 91 respondents (32 male and 59 female) were involved to thestudy comprises of two different educational backgrounds (59 Diploma III and 32Bachelor degree). The statistical analysis using Pearson correlation found thatworkload (0.003), working condition (0.000), quality of nursing work life (0.000),perceived organizational support (0.000) significantly correlated to job stressamong ICU nurses.Conclusion: All studied factors correlated to job stress among ICU nurses. Allfactors had moderate correlation with nurses’ job stress and working condition hashighest strong correlation compare to the other factors. Its implies from the resultthat management of the hospital may provide more attention to job stress amongnurses to maintain optimum performance to provide nursing care for patientsparticularly critically ill patients in ICU.